Cleaner approach for medium consistency eucalyptus slab pulp production using ozone bleaching under turbulent mixing. (10th December 2020) - Zhang, Xi; Li, Jun; Gong, Jie; Kuang, Yishan; He, Shuaiming; Xu, Jun; Mo, Lihuan; Man, Yi; Zhu, Wenyuan; Song, Junlong; Song, Tao
Abstract: Eucalyptus slab (ES), a cellulosic waste from wood processing is abundant and can be utilized for the pulping in many wood scarce countries. However, during chlorine dioxide (ClO2 ) bleaching, which is the current applied bleaching technique for medium consistency eucalyptus slab pulp (MC-ESP), toxic absorbable organic halides (AOX) is still generated, causing pollution to the water environment. Applying ozone gas (O3 ) to replace ClO2 for MC-ESP bleaching is a promising alternative way since O3 is a clean and powerful oxidizing agent but not producing AOX pollutant. In this work, the influences of the three most important O3 -bleaching factors, i.e., O3 -concentration, O3 -dosage and mixing intensity to the bleaching properties of MC-ESP was systematically evaluated. It was found that increasing of O3 -concentration and O3 -dosage greatly improved the properties of MC-ESP. Turbulent mixing intensity had a effective effect on improving O3 -bleaching of MC-ESP. The high O3 -concentration (170 mg/L), 1.0% O3 -dosage and 1200 rpm rotational speed were found to be optimum conditions for O3 -bleaching of MC-ESP. Under this condition, the brightness, kappa number and viscosity of the pulp obtained were similar or even better than those of the ESP after bleaching with similar or higher ClO2 -dosage, however, without generating toxic AOX and with lower pollution load of effluent. This research provided important supports for the development of MC-ESP cleaner production by reducing the pollutant from ClO2 bleaching. Such approach of using wood processing waste as raw material, O3 gas as AOX-free bleaching agent could provide the excellent options for eco-friendly pulp production. Highlights: Eucalyptus slabs is an important wood processing waste in many countries. Using of Eucalyptus slabs for pulp production is a high-value-added applications. ClO2 -bleaching generates a lot of toxic absorbable organic halides (AOX). O3 is a powerful oxidizing agent but not producing AOX pollutant. Using O3 for cleaner production of medium consistency eucalyptus slab pulp is a feasible way.